POLIGAMI DALAM PERSPEKTIF AL-QUR`AN - Isti'anah, Isti'anah (IAINU Kebumen Prodi IAT, 2022)
The practice of polygamy has existed long before Islam and has become a permissible custom. Unfortunately, many people assume that polygamy is a practice that was only known after the arrival of Islam. Ironically, Islam is considered to monopolize and legalize polygamy. In reality, Islam came by providing restrictions on polygamous marriages with certain limitations. Justice in polygamy is an obligation that must receive special attention, because the word